Goldenhar's Syndrome (A Case Report) - S. Bhattacharya; S. K. Bhatnagar; R. Chandra (Indian Journal of Plastic Surgery)
Goldenhar's syndrome or occulo-auriculo-vertebral dysplasia is characterized by the presence of abnormalities of the first and second branchial arches accompanied by apibulbar dermoids or lipodermoids and vertebral anomaties. Other associated congenital anomaties may be frequently present. A case of Goldenhar's syndrome with macrostomia, transverse facial cleft and telepes calcaneovalgus deformity is being presented.